Judaism in the beginning of Christianity - Nuesner, Jacob, 1932-2016 (Philadelphia : Fortress Press, 1984)
In this book Jacob Neusner answers the central questions about the world of Judaism in which Christianity was born. He gives an overview of the history and religion of Israel and an analysis of the Judaic legacy as it endured among those who did not become Christians.
Judaism beyond catastrophe: the destruction of the Temple and the renaissance of Torah.
Includes bibliographical references and index.
Keywords: Hillel, active 1st century B.C. - 1st century A.D.; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.; Judaism -- Relations -- Christianity; Christianity and other religions -- Judaism